A Synergistic Genetic Engineering Strategy Induced Triacylglycerol Accumulation in Potato (Solanum tuberosum) Leaf - Xu, Xiao-yu; Akbar, Sehrish; Shrestha, Pushkar; Venugoban, Lauren; Devilla, Rosangela; Hussain, Dawar; Lee, Jiwon; Rug, Melanie; Tian, Lijun; Vanhercke, Thomas; Singh, Surinder P.; Li, Zhongyi; et al. (Frontiers in Plant Science, 2020)
Potato is the 4th largest staple food in the world currently. As a high biomass crop, potato harbors excellent potential to produce energy-rich compounds such as triacylglycerol as a valuable co-product. We have previously reported that transgenic potato tubers overexpressing WRINKLED1, DIACYLGLYCEROL ACYLTRANSFERASE 1 and OLEOSIN genes produced considerable levels of triacylglycerol. In this study, the same genetic engineering strategy was employed on potato leaves. The overexpression of Arabidopsis thaliana WRINKED1 under the transcriptional control of a senescence-inducible promoter together with Arabidopsis thaliana DIACYLGLYCEROL ACYLTRANSFERASE 1 and Sesamum indicum OLEOSIN driven by the Cauliflower Mosaic Virus 35S promoter and small subunit of Rubisco promoter respectively, resulted in an approximately 30- fold enhancement of triacylglycerol in the senescent transgenic potato leaves compared to the wild type. The increase of triacylglycerol in transgenic potato leaves was accompanied by perturbations of carbohydrate accumulation, apparent in a reduction in starch content and increased total soluble sugars, as well as changes of polar membrane lipids at different developmental stages. Microscopic and biochemical analysis further indicated that triacylglycerol and lipid droplet could not be produced in chloroplasts, despite the increase and enlargement of plastoglobuli at the senescent stage. Possibly enhanced accumulation of fatty acid phytyl esters in the plastoglobuli were reflected in transgenic potato leaves relative to wild type. It is likely that the plastoglobuli may have hijacked some of the carbon as the result of WRINKED1 expression, which could be a potential factor restricting the effective accumulation of triacylglycerol in potato leaves. Increased lipid production was also observed in potato tubers, which may have affected the tuberization to a certain extent. The expression of transgenes in potato leaf not only altered the carbon partitioning in the photosynthetic source tissue, but also the underground sink organs which highly relies on the leaves in development and energy deposition.